Effect of Indomethacin on Surface Treatment and Intracanal Dressing of Replanted Teeth in Dogs - Zanetta-Barbosa, Darceny; Gomes Moura, Camilla Christian; Machado, Juliana Reis; Crema, Virginia Oliveira; Paula Lima, Cirilo Antonio de; Perry de Carvalho, Antonio Cesar [UNESP] (Elsevier B.V., 2014)
Purpose: This study evaluated the healing process of teeth replanted after root treatment and intracanal dressing with indomethacin alone or indomethacin with calcium hydroxide (Ca[OH](2)).Materials and Methods: Through a case-control study, 24 teeth of 6 adult dogs were extracted, dried, and divided into 4 groups according to the root surface treatment protocols performed before replantation and the intracanal medication used after replantation. In group 1 (negative control), root surfaces were treated by immersion in a 0.9% saline solution and then replanted. In the other groups, the roots were immersed for 10 minutes in Ca(OH)(2) (group 2), indomethacin (group 3), or a solution of indomethacin and Ca(OH)(2) (group 4). After 2 weeks, group 1 teeth were subjected to single-visit root canal treatment and obturation with gutta-percha and sealer consisting of zinc oxide and eugenol. The teeth in the other groups were subjected to intracanal dressing with the same material used for immersion. After an additional period of 28 weeks, the animals were euthanized and the jaws containing the replanted teeth were processed for histologic analysis. Histometric values were statistically analyzed, with significance set at a P value less than or equal to .05.Results: Group 1 exhibited significantly more normal periodontium than group 4 (P = .02). Total resorption was greater in group 4 than in group 1 (P = .02). No statistically significant difference in the percentage of surface resorption or in total inactive resorption was observed between the groups.Conclusions: The findings of this study suggest that intracanal dressing and topical root treatment with Ca(OH)(2) with or without indomethacin is not recommended for teeth dried for 50 minutes, but the use of indomethacin alone as root surface treatment for delayed tooth replantation deserves further study using longer drying periods. In addition, the present results suggest that a single-visit root canal, performed up to 2 weeks after replantation, might be indicated for teeth dried for up to 50 minutes. (C) 2014 American Association of Oral and Maxillofacial Surgeons